Dampak Kebijakan Penggunaan Kartu Pas Lintas Batas Di Desa Silawan Kecamatan Tasifeto Timur Kabupaten Belu - Gregorius Dwartu Bere; Yeftha Y. Sabaat; Stefanus Tri Admaja (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2026)
The Cross-Border Pass is a travel document that functions similarly to a passport and visa for residents living in the land border areas between Indonesia and Timor-Leste. This study aims to identify and describe the impact of the Cross-Border Pass Card (KPLB) policy in Silawan Village, East Tasifeto Subdistrict, Belu Regency. This research employs a descriptive method with a qualitative approach. Data were collected through in-depth interviews, observation, and documentation. The results of the study, based on William N. Dunn’s policy evaluation theory, indicate that the KPLB policy has a positive impact in facilitating community mobility in a legal, orderly, and secure manner, as well as supporting social and economic activities in border areas. However, in terms of adequacy, the policy has not fully met the needs of the community, as there are still residents who do not possess the card and face limited access to services. In addition, several challenges were identified in the implementation of the policy, including limited socialization, inadequate supporting facilities and infrastructure, and the potential misuse of the card for illegal activities such as smuggling.